ALIGNING PRAXIS OF FAITH AND THEOLOGICAL THEORY IN THEOLOGICAL EDUCATION THROUGH AN EVALUATION OF CHRISTIANITY IN SOUTH AFRICA - E. Oliver (Acta Theologica)
Having to cope in the revolution-driven world of the 21st century as well as the new-normal COVID-19 society brought theology to yet another crossroad. Theology (both theory and praxis) must react positively to the changes and lessons learned from some of the major revolutions. Just as the Fourth Industrial Revolution blurs the distinctive lines between physical, digital, and biological, so should the separated boxes of personal faith, institutionalised religion, and spirituality be wiped out. Human self-awareness helps us know ourselves and improve our ability to glorify God, while the Communication Revolution empowers Christians to spread the gospel globally. Christianity is also in need of a revolution back to its origin of an un-institutionalised, non-hierarchical, living faith that is changing the lives of people both in the present and eternally. From a South African perspective, the article evaluates the major mistakes that Christians made, some achievements on which they could build and expand, and the ideals that should pave the way forward. It is time to ask some hard questions and provide appropriate answers in the quest for Christian renewal.